Real Estate Bubbles in China's Mega Cities - Government Policies and Lessons for Vietnam - Phuong Lan, Le; Thi My Linh, Nguyen; Hang Khanh Linh, Doan; Hoang Mai, Nguyen; Tu Hieu Ngan, Nguyen; Thien An, Chu; Thi My Anh, Nguyen (VNU Journal of Science: Policy and Management Studies, 2026)
This study uses a comparative, qualitative case study approach to analyze the dynamics of real estate bubbles in China’s megacities and draw relevant policy lessons for Vietnam. Based on secondary data sources, the study is conducted in two phases. In the first phase, the study confirms the existence of real estate bubble cycles in major cities in China and Vietnam, highlighting the core commonality of asset prices being decoupled from economic fundamentals. In the second phase, the study analyzes the Chinese government’s policy intervention portfolio, notably home purchase restrictions, credit (tightening lending), and property tax pilots. The expected result is that although these policies in controlling speculation are effective, they also cause unintended fiscal consequences at the local level.  By comparing the institutional contexts between the two countries, the study identifies policy instruments that could be applied in Vietnam, while emphasizing the need for long-term, locally relevant solutions rather than short-term measures.